ANTIBACTERIAL ACTIVITY OF BENZIMIDAZOLES 2-THIO, 2-AMINODERIVATIVES AND COMPLEXES OF BENZIMIDAZOLES WITH TRANSITIONAL METALS - E. I. Mayboroda; V. N. Britsun (Фармация и фармакология (Пятигорск))
The literature data about antibacterial properties of benzimidazole 2-thio-, 2-aminoderivatives and benzimidazole complexes have been generalized and systematized in the review. Today prevention and treatment of diseases caused by microorganisms is an actual problem of modern therapy. Therefore, the search for active molecules, the based on them development of some new, more effective antimicrobial agents is an important task of modern pharmaceutical chemistry. Promising compounds for solving these problems are benzimidazole derivatives. They are available, functionally capable, stable and have a wide spectrum of biological activities (antiviral, anthelmintic, antibacterial, anticancer, antidiabetic).The purpose of this paper is to generalize and systematize information about the antimicrobial action of 2-thio-, 2-amino-substituted benzimidazoles and benzimidazole derivatives complexes with transition metals.These compounds and their complexes with transition metals are active against pathogenic strains Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Salmonella typhimurium, Proteus vulgaris, Bacillus cereus, Micrococcus luteus, Helicobacter рylori and others.